Synthesizing Itqan Values and Total Quality Management (TQM) in Enhancing Customer Satisfaction at Elementary School: A Conceptual Literature Review - Aanisah Agusnani Rizq; Hilmi Qosim Mubah; Oki Darmawan (re-JIEM (Research Journal of Islamic Education Management), 2026)
This conceptual literature review examines the theoretical integration of Total Quality Management (TQM) principles with Islamic Itqan (professionalism) and Ahsanu ‘Amala (excellence) values to map customer satisfaction in Islamic elementary education. Rather than reporting empirical implementation, the study synthesizes scholarly and Islamic literature to construct a conceptual framework that aligns managerial quality standards with spiritual and character development objectives. Through systematic analysis of relevant publications, the review identifies five core TQM principles (customer focus, total involvement, continuous improvement, visionary leadership, and data-driven decision-making) and recontextualizes them within Islamic educational ethics. The synthesis demonstrates that stakeholder satisfaction emerges when academic quality benchmarks are harmonized with moral and spiritual formation. The review further emphasizes that standard operating procedures (SOPs) are not merely administrative tools, but operational expressions of the Islamic principle of mizan (balance and fairness) in service delivery. By mapping the intersection of modern quality management and Islamic work ethics, this paper offers a conceptual foundation for Islamic elementary schools to synchronize national standards with institutional religious values. It concludes that ethically grounded standardization provides a structured pathway to sustain public trust and service consistency.